MTHFR Gene Polymorphism Association With Psoriatic Arthritis Risk and the Efficacy and Hepatotoxicity of Methotrexate in Psoriasis - Zhu, Jie; Wang, Zhicheng; Tao, Lu; Han, Ling; Huang, Qiong; Fang, Xu; Yang, Ke; Huang, Guiqin; Zheng, Zhizhong; Yawalkar, Nikhil; Zhang, Zhenghua; Yan, Kexiang (Frontiers in Medicine, 2022)
Aims: To assess whether MTHFR rs1801131 and rs1801133 SNPs are associated with concomitant psoriatic arthritis (PsA) and investigate the efficacy and hepatotoxicity of MTX in patients with psoriasis in the Han Chinese population. Methods: This prospective, single-arm, interventional study recruited a total of 309 patients with psoriasis, 163 with psoriatic arthritis and 146 without psoriatic arthritis, who completed a 12-week MTX treatment and 1031 healthy controls. Patients’ characteristics including age, gender, disease duration, height, weight, smoking status, alcohol consumption, medical history, disease severity and liver function test results were accessed and recorded. Single nucleotide polymorphism (SNP) genotyping of rs1801131 and rs1801133 in the MTHFR gene was performed. Results: The rs1801133 CC genotype was more frequent in patients with PsA than those with PsO and healthy controls (42.3% vs. 28.8% vs 33.1%, p<0.05). The 90% reduction from baseline PASI score (PASI 90) response rates to MTX were significantly higher in patients with the rs1801133 TT genotype than those with the CT and CC genotype (33.96% vs. 19.31% vs. 14.41%, OR = 2.76, p = 0.006). The rs1801133 CT+TT genotype was more frequent in PsA patients with abnormal liver function than in those with normal liver function (p < 0.05). In addition, patients with the rs1801131 CT genotype had lower PASI 75 response rates to MTX (OR = 0.49, p = 0.01), and lower risk of ALT elevation (OR = 0.46, p = 0.04). Conclusions: This study provided some evidence for MTHFR polymorphism association with the risk of PsA and the efficacy and hepatotoxicity of the low-dose MTX in the Chinese population. Given the relatively small sample size and potentially missed diagnosis of PsA, the results from this study warrant further investigation. Funding: National Natural Science Foundation of China, Science and Technology Commission of Shanghai Municipality, Shanghai Shen Kang Hospital Development Center.